Regional Analysis of Sheep Business in Banjarnegara Regency - E. Gustia; S. Mulatsih; A. Gunawan (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
Banjarnegara Regency is home to the local Batur sheep, known for their significant body weight. The community has been raising Batur sheep for generations, aiming to develop them into a regional economic driver. This study aims to analyze potential areas for sheep livestock development in Banjarnegara Regency. The data used came from the farm statistics of the Directorate-General for Farm and Animal Health in 2021. The location quotient (LQ), localization index (LI), and specialization index (SI) method were used to perform regional analysis of sheep business. The results of the survey showed that the base area of sheep farming in Banjarnegara district is distributed in the districts of Karangkobar, Pejawaran, Batur, and Wanayasa. The localization and specialization index showed that sheep farming is spread evenly throughout the district of Banjaregara, not concentrated in a particular region.